The contribution of electrostatic interactions to the collapse of oligoglycine in water - Karandur, D.; Pettitt, B.M. (Condensed Matter Physics, 2016)
Protein solubility and conformational stability are a result of a balance of interactions both within a protein and between protein and solvent. The electrostatic solvation free energy of oligoglycines, models for the peptide backbone, becomes more favorable with an increasing length, yet longer peptides collapse due to the formation of favorable intrapeptide interactions between CO dipoles, in some cases without hydrogen bonds. The strongly repulsive solvent cavity formation is balanced by van der Waals attractions and electrostatic contributions. In order to investigate the competition between solvent exclusion and charge interactions we simulate the collapse of a long oligoglycine comprised of 15 residues while scaling the charges on the peptide from zero to fully charged. We examine the effect this has on the conformational properties of the peptide. We also describe the approximate thermodynamic changes that occur during the scaling both in terms of intrapeptide potentials and peptide-water potentials, and estimate the electrostatic solvation free energy of the system. Розчиннiсть та конформацiйна стабiльнiсть протеїну є результатом балансу взаємодiй як в межах протеїну, так i мiж протеїном та розчинником. Вiльна енергiя електростатичної сольватацiї олiгоглiцинiв,
моделей для хребта протеїну, стає бiльш вигiдною iз зростанням довжини, до того ж довшi пептиди колапсують через формування вигiдних внутрiпептидних взаємодiй мiж диполями CO, в деяких випадках
без водневих зв’язкiв. Сильно вiдштовхувальне формування розчинникової порожнини збалансовується
ван дер вальсiвським притяганням та електростатичними внесками. Для того, щоб дослiдити конкуренцiю мiж виключенням розчинника та зарядовими взаємодiями, ми моделюємо колапс довгого олiгоглiцину з 15-ма блоками при скейлiнгу зарядiв на пептидi вiд нуля до повного заряду. Ми вивчаємо, який ефект
це має на конформацiйнi властивостi пептиду. Ми також описуємо приблизнi термодинамiчнi змiни, що
вiдбуваються пiд час скейлiнгу як через iнтрапептиднi потенцiали, так i через потенцiали пептид-вода, i
визначаємо вiльну енергiю електростатичної сольватацiї для системи.